Muhammad: the ideal prophet - Saiyid Sulaiman Nadwi; Mohiuddin Ahmad (Islamic Book Trust Kuala Lumpur, 1977)
Muhammad: The Ideal Prophet examines the life and character of Prophet Muhammad as a model of virtue, leadership, and compassion for humanity.